Innovation In Education Management To Improve Learning Quality - Ahmad Rahman Budiman; Syafril Barus; Petrus Jacob Pattiasina; Syarifuddin Syarifuddin; Hudson Sidabutar (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
Innovation in education management is essential to improve the quality of learning in an ever-evolving era. This study uses the literature method. The results show that innovative strategies that can be implemented by educational institutions to improve student engagement and the effectiveness of the learning process include the utilisation of digital technology, teacher professional development and collaboration with external stakeholders. Then, to implement these strategies, there are common challenges such as resistance to change and budget constraints that can be a barrier to implementing innovation. With a comprehensive and planned approach, as well as high commitment from all members of the organisation, these innovations are expected to provide significant improvements to the quality of education and student learning outcomes.